Privacy And Detecting Malicious Packet Dropping In Wireless Ad Hoc Network (International Journal of Engineering and Computer Science, 2015)
Packet dropping is common attacks occur in wireless Ad hoc Network. This threat occurs when the data is transmitted from one source to destination. The attack may be classified into two types one is malicious packet dropping. And another one is link error. This can be overcome by the proposed scheme by implementing Homomorphic Linear Authenticator (HLA). It is the public auditing scheme to detect the malicious node in WANET. HLA act like an auditor to detect the packet losing schemes in the network. The main advantage of this scheme will securely transmit the data in WANET. The packet dropping rate is comparable to the channel error rate, conventional algorithms that are based on detecting the packet loss rate cannot achieve satisfactory detection accuracy. To improve the detection accuracy, the correlations between lost packets is identified. HLA based public auditing architecture is developed to verify the truthfulness of the packet loss information reported by nodes. Thus the implementation is useful to avoid packet dropping attack in Wireless Ad hoc Network